Endoscopic Balloon Dilatation for the Treatment of Caustic Induced Pyloric Strictures - Mashood Ali, Arslan Shahzad, Inayatullah Khan Adil,Haseeb Noor, Shan Alam, Asif Imran,NaveedGani (Journal of Rawalpindi Medical College, 2016)
Background: To study the role of endoscopic balloon dilatation, as a cost effective and safe method, for the treatment of caustic induced pyloric strictures. Methods: In this descriptive study 28 consecutive patients who presented with caustic ingestion and were enrolled for endoscopic ballon dilatation were included. Patients with complete pyloric channel occlusion ,and long, tortuous strictures were excluded. All patients were admitted to hospital before starting dilatations. Barium X-rays were performed to rule out complete obstruction and to assess the length of stricture and patients with complete obstruction and long tortuous strictures were excluded. Intravenous fluids/Total Parenteral Nutrtion and Proton pump inhibitors were given where necessary. Procedures were carried out under conscious sedation during endoscopy without fluoroscopic monitoring. Through the scope balloons of varying sizes, with the advantage that the same balloon can be dilated to different diameters) (12.5 to 18 mm) were used. The time for dilation was 4 to 12 weeks after caustic ingestion. Results: The average age of the participants was 21 years. There was a female preponderance with 82% females. The average number of dilatations were 4, with a range of 1 to 12. Successful dilatation both early and late were 82.6% while 17.4% were unsuccessful. Only 1(3.6%) case of perforation was reported which was managed conservatively. Bleeding was seen in 53.6% cases, which was minor and self limiting. Mild pain was reported in 30% of the cases. Conclusion: Endoscopic Balloon Dilatation is a safe and effective mode of treatment and suitable alternative to surgery in selected cases of caustic induced pyloric stenosis.